Pengembangan Desa Wisata Bumi Arum Majasto berbasis Histori, Lingkungan, dan Ekonomi - Indrawati, Indrawati; Nurhasan, Nurhasan; Hidayati, Rini; Nugrahaini, Fadhilla Tri; Haryanti, Dwi; Musthofa, Zaini (Warta LPM, 2023)
Majasto village was designated by the government as a Religious Tourism Area through the Sukoharjo Regency Spatial Plan. However, to support this, Majasto Village does not have a good management system and regional planning of village-owned enterprises (Badan Usaha Milik Desa/Bumdes) to encourage its economic acceleration. This program aims to develop a tourism village area plan and optimal financial management for Bumdes. The method used is through mapping both physical and non-physical potentials of the village to obtain detailed information, which is done by conducting a mapping or survey to identify natural and artificial physical potential, as well as socioeconomic and historical aspects to understand the potential and problems through SWOT analysis. The results of this program are in the form of a Tourism Village Master Plan and a Priority Area Plan. The second result is the initiation of financial digitization training through Bumdes Financial Accounting System. This is done to ensure that Bumdes can record transactions and financial reporting properly. The integration of the development of Bumdes business unit based on the Tourism Village Master Plan and the Priority Area Plan (the first stage result) and the Bumdes Profile (the second stage result).